Workforce crisis in primary healthcare worldwide: Hungarian example in a longitudinal follow-up study - Papp, Magor (BMJ Open, 2019)
OBJECTIVE: The study was designed to explore the development of the general practitioner (GP) shortage in primary care and its characteristics in Hungary. DESIGN: Longitudinal follow-up study over the decade 2007–2016. METHODS: Analyses were performed on changes in number, age and sex of GPs by practice type (adult, paediatric and mixed), as well as on their geographical distribution and migration between areas characterised by deprivation index (DI) at municipality level. The association between deprivation and vacancy for GPs was studied by risk analysis. The number of population underserved was defined by DI quintile. SETTING AND SUBJECTS: The study involved all general practices and GPs in the period examined. MAIN OUTCOME MEASURE: It is showed that the number of general practices with unfilled GP posts was increasing exponentially, mainly in the most deprived areas of the country. RESULTS: A decrease in the number of GPs in all types of practices, especially in mixed (by 7.7%; p<0.001) and paediatric (by 6.5%; p<0.001) ones, was shown; the number of adult practices with unfilled GP posts doubled, while the number of paediatric practices with a vacancy for a paediatrician more than tripled. The average age of GPs was increased by 3.7 years (p<0.001) in adult, by 5.4 years (p<0.001) in paediatric and by 4.2 years (p<0.001) in mixed practices. In 2007, 52.27% (95% CI 51.03 to 53.5) of the GPs were women, and this rate increased to 56.19% (95% CI 54.93 to 57.44) by the end of the decade. An exponential association between relative vacancy rate and deprivation was confirmed. As a result of the migration of GPs, in the most deprived areas, the number of GPs decreased by 8.43% (95% CI 5.86 to 10.99). CONCLUSIONS: The workforce crisis in Hungarian primary care is progressively deepening and resulting in more severe inequity in access to healthcare.